Public Space, between Regulations and Informality: A Tale of Two Cities , San José (Costa Rica) and Bogotá (Colombia) - Víquez Abarca, Rosibel (2016)
This paper discusses the use and appropriation of public space deriving from the dialogue between two research projects which come from different contexts and had different social actors, this to show the diversity of approaches, their potential and also their weaknesses both in San Jose and Bogota. On one hand, the way young people in San Jose city centre use such spaces against a "City Guide" approach, and on the other hand, the use which inhabitants of working-class neighborhoods in Bogotá give to their public spaces. Both research projects identify relationships weaved between space and its inhabitants, and between the inhabitants themselves and the different social actors, including The State, from which there are lessons on regulations and informality that could be part of the study or even the projection of our Latin American cities. These lessons can also end up in conflicts and intricate power-relations.